KEPATUHAN LANSIA PENDERITA HIPERTENSI DALAM PEMENUHAN DIET HIPERTENSI - Agrina, Agrina; Rini, Sunarti Swastika; Hairitama, Riyan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The purpose of this study was to know about pursuance of hypertension elderly incomplience diet hypertension . The research was conducted in the working area Sidomulyohealth care center, in the Village of West Sidomulyo, Pekanbaru City. The respondents inthis study is 60 people with purposive random sampling method . This study is the simpledescriptive design with Cross-Sectional approach. The data is collected by questionnaires.The analysis data by univariat in frequency distribution to know pursuance of hypertensionelderly in complience diet hypertension. The result is study that found that 26 people(43,3%) the hypertension elderly are pursuance in diet hypertension and 34 people (43,3%)the hypertension elderly aren’t pursuance in diet hypertension. Recomendation to healthworkers to provide counseling about hypertension specially about diet of hypertension, so theincidence of hypertension can be reduced significantly.